REGIONAL STAKEHOLDER WORKSHOP ON CLIMATE SMART AGRICULTURE INVESTMENT PLANNING: An Implementation Roadmap for Eastern and Southern Africa - Jalango, Dorcas Anyango; Yaregal, Yodit; Tesfaye, Lidya Ayalew; Ogutu, Elizabeth; Makonnen, Brook (2024)
This report, Implementation of Climate-Smart Agriculture Investment Plans: A Roadmap for Eastern and Southern Africa, provides a strategic framework to operationalize Climate-Smart Agriculture Investment Plans (CSAIPs) in Kenya, Ethiopia, and Zambia. The report identifies key implementation barriers, including financial constraints, fragmented coordination, and inadequate capacity, while offering phased solutions to address these challenges. The roadmap emphasizes resource mobilization through blended finance, private sector engagement, capacity building, and policy alignment to foster sustainable CSA adoption. It highlights the importance of multi-stakeholder platforms and regional collaboration to harmonize strategies and scale efforts across the continent.